Tema Post-Modern pada Perencanaan Desain Stasiun Intermoda LRT (Light Rail Transit) Joyoboyo sebagai Local Icon di Surabaya - Dian Arminda; Siti Azizah (Institut Teknologi Adhi Tama Surabaya, 2020)
Abstract. As we know, Surabaya occupies the second position as a city that has the most populous vehicle volume after Jakarta. Lack of public transportation services makes people choose to use private vehicles and even online transportation which of course will just cause traffic jams. Some things that make people less use public transportation include low levels of comfort, safety, punctuality, and discipline in driving, as well as inadequate transportation. Congestion is triggered by the increasing number of vehicles and is not comparable with the development of existing infrastructure. Of the many problems that have arisen, the central government and regional governments plan for an adequate and mass-based transportation infrastructure namely LRT (Light Rail Transit) that is able to transport passengers in large numbers, fast, and rail-based that is able to give the impression of being safe, comfortable, and clean. Comfort for passengers is not only when riding the LRT train, but at the station. The station is made as comfortable as possible so that it can attract visitors to prefer using public transportation rather than private vehicles or online transportation by providing facilities in the form of commercial areas and other supporting facilities. Macro concept on LRT Station design carries a concept of